2019
DOI: 10.1186/s12870-019-2090-6
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The role of seed appendage in improving the adaptation of a species in definite seasons: a case study of Atriplex centralasiatica

Abstract: BackgroundAs a common accompanying dispersal structure, specialized seed appendages play a critical role in the successful germination and dispersal of many plants, and are regarded as an adaptation character for plants survival in diverse environments. However, little is known about how the appendages modulate the linkage between germination and environmental factors. Here, we tested the responses of germination to seasonal environmental signals (temperature and humidity) via seed appendages using Atriplex ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…T. ramosissima seeds are extremely small and have hairy appendages ( Zhang et al . 2002 ), which are considered adaptations for survival in adverse environments ( Wang et al . 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…T. ramosissima seeds are extremely small and have hairy appendages ( Zhang et al . 2002 ), which are considered adaptations for survival in adverse environments ( Wang et al . 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dead coverings of seeds from different species are very diverse and reflect the adaptive characteristics of seed dispersion in a variety of different environments (Webb et al 2009, Wang et al 2019. Previous studies have exported the effect of dead layers on seed germination was species-specific, and showed that dead coverings could increase (Ueno and Miyoshi 2005), decrease (Fandrich and Mallory-Smith 2006), or have no influence on seed germination characters.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted on the ecology of species with dimorphic diaspores (reviewed in Baskin et al 2013 , 2014 ). However, there are fewer such studies on species that produce three diaspores ( Venable et al 1987 ; Wei et al 2007 ; Wang and Wei 2007 ; Cheng and Tan 2009 ; Sun et al 2008 , 2009 ; Ma et al 2018 ; Mamut et al 2018 ; Wang et al 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%